Answer:
The equations that represent the reflected function are
![f(x)=5(\frac{1}{5})^{-x}](https://tex.z-dn.net/?f=f%28x%29%3D5%28%5Cfrac%7B1%7D%7B5%7D%29%5E%7B-x%7D)
![f(x)=5(5)^{x}](https://tex.z-dn.net/?f=f%28x%29%3D5%285%29%5E%7Bx%7D)
Step-by-step explanation:
The correct question in the attached figure
we have the function
![f(x)=5(\frac{1}{5})^{x}](https://tex.z-dn.net/?f=f%28x%29%3D5%28%5Cfrac%7B1%7D%7B5%7D%29%5E%7Bx%7D)
we know that
A reflection across the y-axis interchanges positive x-values with negative x-values, swapping x and −x.
therefore
![f(−x) = f(x).](https://tex.z-dn.net/?f=f%28%E2%88%92x%29%20%3D%20f%28x%29.)
The reflection of the given function across the y-axis will be equal to
(Remember interchanges positive x-values with negative x-values)
![f(x)=5(\frac{1}{5})^{-x}](https://tex.z-dn.net/?f=f%28x%29%3D5%28%5Cfrac%7B1%7D%7B5%7D%29%5E%7B-x%7D)
An equivalent form will be
![f(x)=5(\frac{1}{5})^{(-1)(x)}=5[(\frac{1}{5})^{-1})]^{x}=5(5)^{x}](https://tex.z-dn.net/?f=f%28x%29%3D5%28%5Cfrac%7B1%7D%7B5%7D%29%5E%7B%28-1%29%28x%29%7D%3D5%5B%28%5Cfrac%7B1%7D%7B5%7D%29%5E%7B-1%7D%29%5D%5E%7Bx%7D%3D5%285%29%5E%7Bx%7D)
therefore
The equations that represent the reflected function are
![f(x)=5(\frac{1}{5})^{-x}](https://tex.z-dn.net/?f=f%28x%29%3D5%28%5Cfrac%7B1%7D%7B5%7D%29%5E%7B-x%7D)
![f(x)=5(5)^{x}](https://tex.z-dn.net/?f=f%28x%29%3D5%285%29%5E%7Bx%7D)
Answer:
The flag pole is 38.96 feet tall.
Step-by-step explanation:
The angle of depression from the top of the flagpole to an object on the ground is 33°.
The object is 60 feet from the base of the cliff.
We need to find the height of the flag pole.
Here, base, B = 60 feet
We know that,
![\tan\theta=\dfrac{P}{B}](https://tex.z-dn.net/?f=%5Ctan%5Ctheta%3D%5Cdfrac%7BP%7D%7BB%7D)
Put all the values to find P.
![P=B\times \tan\theta\\\\P=60\times \tan(33)\\\\P=38.96\ ft](https://tex.z-dn.net/?f=P%3DB%5Ctimes%20%5Ctan%5Ctheta%5C%5C%5C%5CP%3D60%5Ctimes%20%5Ctan%2833%29%5C%5C%5C%5CP%3D38.96%5C%20ft)
So, the flag pole is 38.96 feet tall.
Answer:
225
Step-by-step explanation:
The sum of this series is given by the formula:
![S_n=\frac{n}{2}[2a+(n-1)d]](https://tex.z-dn.net/?f=S_n%3D%5Cfrac%7Bn%7D%7B2%7D%5B2a%2B%28n-1%29d%5D)
Where
S_n is the sum
a is the first term (we get this by plugging in n = 1 into "2n-1", we have 2(1) - 1 = 1)
n is the number of terms (the sum is defined for n = 1 to n = 15, so 15 terms)
d is the common different (the difference is successive terms. Here, 2nd term would be 2(2) - 1 = 3, and first term was 1, so d = 3 -1 = 2)
<em>plugging in the info, we will get the sum:</em>
<em>
</em>
<em>The sum is 225</em>
Answer:
1 1/5
Step-by-step explanation:
Answer:
the answer x algorithm happy fail day